Symptoms of exhibitionism that regress with bupropion: A case report - Vayısoğlu, Sefa (Frontiers in Psychiatry, 2023)
Exhibitionistic Disorder, one of the paraphilic disorders, is a disease with an unknown aetiology and causes significant distress and loss of function in the patient's life. Serotonergic antidepressants are generally preferred in the treatment of this Disorder. However, in this case, we report a patient who did not respond to serotonergic antidepressants but bupropion, an antidepressant with dopaminergic and noradrenergic activity. Therefore, bupropion should be considered a medical treatment alternative in case serotonergic antidepressants do not work efficiently in the treatment of Exhibitionism.